PENGARUH MODEL GAMIFIKASI DENGAN MEDIA CANVA EDU TERHADAP MOTIVASI DAN KEAKTIFAN BELAJAR PADA MATA PELAJARAN MATEMATIKA SISWA KELAS IV DI SEKOLAH DASAR NEGERI TANJUNG 2 KECAMATAN JUWIRING KABUPATEN KLATEN (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the influence of gamification learning model with Canva Edu media on students' motivation and learning activity in mathematics subjects. This study uses a quantitative approach with a pretest-posttest design of one group. The research sample amounted to 23 elementary school grade IV students. The data collection technique uses a questionnaire on motivation and learning activity that has been tested for validity and reliability. Data analysis used descriptive statistics, Wilcoxon Signed Rank Test normality test, and hypothesis test using Paired Sample T-Test. The results showed that the average student learning motivation increased from 22.57 at the time of the pretest to 33.04 at the time of the posttest, while the average score of learning activity, which was from 25.22 at the time of the pretest, increased to 33.22 at the time of the posttest. The results of the hypothesis test showed a significance value of 0.001 < 0.05 so that H0 was rejected and H₁ and H₂ were accepted. This shows that there is a significant influence of the gamification learning model with Canva Edu media on students' motivation and activeness of learning. Thus, the use of gamification with Canva Edu media can increase student engagement and make learning more engaging and enjoyable.